Prevalence of periodontal bacteria in saliva of Kuwaiti children at different age groups - Vincent O. Rotimi; Nathanael O. Salako; Mary Divia; Linda Asfour; Eija Kononen (Elsevier, 2010)
Summary: Aggregatibacter (formerly Actinobacillus) actinomycetemcomitans, Tannerella forsythensis and Porphyromonas gingivalis and to a lesser extent Prevotella intermedia and Prevotella nigrescens, are Gram-negative species that are associated with destructive periodontitis. Studies from different parts of the world have shown variable detection rates of periodontal organisms. Hardly any data exist on their carriage in children living in the Middle East. This study was designed to determine the detection of these species in the oral cavity of 240 generally healthy Kuwaiti children, divided into five age groups: <6 years (n = 40), 6-9 years (n = 60), 10-12 years (n = 40), 13-15 years (n = 40) and 16-18 years (n = 60). Saliva was used as the microbiological specimen, and the samples were analyzed by molecular methods using multiplex PCR. A total of 185 (77.1%) of the 240 children were colonized by at least one of the target periodontal bacteria. In all age groups, P. nigrescens was the most prominent and detected in saliva of 15%, 32%, 63%, 50%, and 47% of the children at the five age groups, respectively. P. gingivalis was detected only occasionally. Only few pathogens were found before the permanent dentition, i.e. at the age of <6 years. The highest carriage rates were from the groups between 6 and 15 years of age. The salivary carriage of the pathogens was essentially similar in the age groups of 10-12 years and 13-15 years. In conclusion, except for P. gingivalis, the examined periodontal pathogens are relatively common findings in Kuwaiti children and colonize the oral cavity from childhood onwards. Keywords: Prevalence, Periondontopathic pathogens, Children, Kuwait